VERIFICATION OF GEOMETRY ON 3D CONFORMAL RADIOTHERAPY TECHNIQUE WITH NASOPHARINGEAL CANCER CASE AT RADIOTHERAPY UNITS RADIOLOGY INSTALLATION DR. SARDJITO HOSPITAL YOGYAKARTA - Kurniadiyah Nuril Izza; Luthfi Rusyadi; Jeffri Ardiyanto (Jurnal Imejing Diagnostik (JImeD), 2018)
Background: Verification of geometry is a process to ensure that the position and volume of the irradiated tumor is the same as planned.Verification is done by comparing the radiographic image information of the Treatment Planning System (TPS) with radiation therapy to be provided on the Electronic Portal Imaging Device (EPID) device. This research is about geometry verification process on 3D conformal radiotherapy technique with nasopharyngeal cancer case at Radiotherapy Unit Radiology Installation Dr.Sardjito Hospital Yogyakarta which aims to know the procedure and shift of geometry verification.Methods: The type of this research is descriptive study with retrospective data. Methods of data collection used are observation, interview and documentation. The subjects consisted of 3 radiotherapists, 1 medical physician and 1 radiation oncologist. The object of the study was nasopharyngeal cancer patients who received radiotherapy with conformal 3D technique with a sample size of 10 patients. Data obtained from observations and interviews were collected and then data reduction and open coding were then presented in the form of quotations, and drawn conclusions and suggestions.Result: The results of this study indicate that the geometry verification procedure is performed on the irradiation fractions 1,2 and 3 then in the 4th fraction we take the average shift of the fractions 1,2 and 3 to obtain the new isocenter point. After obtaining the new isocenter point of verification, do it again when the fractional radiation to 10 and 20. The average variation of the geometry shift obtained is on the vertical axis of 0.46 cm (towards the posterior), on the longitudinal axis of -0.2 cm (towards the superior) and on the lateral axis of -0.2 cm (towards the left) from the isocenter point.Conclusion: know the procedure of geometry verification conducted in Radiotherapy Unit of Dr. Sardjito Yogyakarta and got the average of shifting variation on each vertical, longitudinal and lateral axis.